Business Strategies for The Most Complex Indonesian Oil Refinery - Nurcahyono, Eko; Prawiraatmadja, Widhyawan (Green Publisher Indonesia, 2025)
Oil (crude) refineries are a fundamental infrastructure of the primary energy in the world. Fuel oil and its derivative products are important commodities needed by society and industry and have always been a concern for every government in the world because of its strategic values (economic, political, and security factors). In Indonesia, the oil and gas industry play a very important role for the nation. In the early days of independence, crude oil was the prima donna of exports commodities and as the foundation of development in Indonesia. But over time, when massive development took place and Indonesia's economy continued to grow into a developing country followed by population growth, this sector was in the spotlight because it was the culprit for contributing to Indonesia's massive import value. Various efforts were made by the Indonesian government to realize energy self-sufficiency so as not to depend entirely on imports, for example through Pertamina as a state-owned enterprise to build the Balongan Refinery. The Balongan refinery was designed and built using the most advanced technology and configurations at the time so that it could process low-cost heavy/very heavy crude oil into a variety of fuels, petrochemicals, and other products. Despite having a highly advanced configuration (11.9 NCI) that far exceeds other domestic refineries as well as refineries in Asia, the Balongan Refinery is under economic pressure from various external factors, such as rising crude oil prices and the preference for higher-priced product types by the market. This research seeks to address and formulate the strategies for the Balongan Refinery to improve its operating performance and economics. The important aspects of the strategy that were researched and evaluated, which were then proposed as the main findings in this study, were the strategy of utilizing potential crude oil alternatives and the strategy of diversifying superior products referring to product price trends in the market. This study also found that flexibility in the selection and processing of potential crude oil by means of an adaptive approach to the actual conditions faced, do not just be strict with design figures, at attractive prices is the key to ensuring the operational and business sustainability of the Balongan Refinery.